Problem-based learning model with Smart Apps Creator media: Effect on students’ fraction problem-solving abilities - Malasari, Fera Laila Nur; Andrijati, Noening (Journal of Educational Management and Instruction (JEMIN), 2024)
Problem solving ability is one of the goals and important elements that students must master during the mathematics learning process. With this in mind, the aim of this research is to test the effectiveness of implementing the Problem Based Learning model assisted by Smart Apps Creator media in developing students' abilities in solving problems regarding fractions in class V. This research took the form of quasi-experiment with a Nonequivalent Control Group Design. The number of students who were the object of this research was 185 students from class V of SDN in Gugus Kenanga, central java province of Indonesia. The sampling method for this research was carried out using a purposive sampling technique. The data collection method were observations and test. The technique for data analysis was carried out using two techniques, namely quantitative analysis and inferential statistics. It was found that there was real difference in students’ ability to solve fraction problems between students who use the Problem Based Learning model using the Smart Apps Creator application and students who use the Problem Based Learning model without using media. From these findings, it can be concluded that there is a significant influence in using the Problem Based Learning model with the help of Smart Apps Creator media in developing the abilities of class V students.